Pengaruh Pengungkapan Corporate Social Responsibility, Good Corporate Governance dan Sales Growth pada Tax Avoidance - Payanti, Ni Made Dwi; Jati, I Ketut (E-Jurnal Akuntansi; Vol 30 No 5 (2020)DO - 10.24843/EJA.2020.v30.i05.p01, 2020)
This study aims to examine the effect of corporate social responsibility disclosure, good corporate governance and sales growth on tax avoidance with a cash effective tax rate (CETR) proxy. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2018 period. Determination of the sample using the nonprobability sampling method with purposive sampling technique obtained by 20 companies with 80 observations. The data analysis technique used is multiple linear regression analysis, first factor analysis is carried out to determine the factors of good corporate governance variables. The results of this study indicate that disclosure of corporate social responsibility has no effect on tax avoidance, good corporate governance with proxies selected representing managerial ownership and institutional ownership negatively affect tax avoidance, while sales growth has a positive effect on tax avoidance. Keywords: Tax Avoidance; Corporate Social Responsibility Disclosure; Good Corporate Governance; Sales Growth.